Study of double parton interactions in diphoton+dijet events in p p collisions at s =1.96 TeV STUDY of DOUBLE PARTON INTERACTIONS in ... V. M. ABAZOV et al. - Abazov, V. M. (2016)
We use a sample of diphoton+dijet events to measure the effective cross section of double parton interactions, which characterizes the area containing the interacting partons in proton-antiproton collisions, and find it to be σeff=19.3±1.4(stat)±7.8(syst) mb. The sample was collected by the D0 detector at the Fermilab Tevatron collider in pp collisions at s=1.96 TeV and corresponds to an integrated luminosity of 8.7 fb-1.